Combined surface modification of commercial aluminum; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Ivanov Yu. F. Yuriy Fedorovich; Lopatin I.; Akhmadeev Yu.; Petrikova E.; Teresov A.; Shugurov V.; Tolkachev O. S. Oleg Sergeevich; Koval N. N. Nikolay Nikolaevich (Physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields, 2017)
Title screen